LEXICO-SYNTACTICAL STYLISTIC DEVICES: SIMILE, PERIPHRASIS, LITOTES, GRADATION, ANTITHESIS, AND REPRESENTED SPEECH - Sotvoldiyeva Nozima,; G’ofurova S.M, (TADQIQOTLAR, 2026)
Annotation This  article  discusses  the  nature  of  lexico-syntactical  stylistic  devices  as  a specific category in linguistics. It examines the aims and functions of devices such as simile,  periphrasis,  litotes,  gradation,  antithesis,  and  represented  speech.  Special attention is paid to how these means intensify speech and create a stylistic effect in modern English.